(3GdCef GdZPGFj GdYQHj (B:s (3ebGQHGJ Gdi UfGYI GdLhY (B/s - (3GdfLaj, SGde Jhajbs ((3HjQhJ(B: s (3eQcR OQGSGJ GdhMOI GdYQHjI(B, s, 2009)
(3GdCef GdZPGFj h YhdeI GdZPGA h GdLhY, GdefXhQ GdJGQjNj ddHjFI GdGbJUGOjI ddCef GdZPGFj, BdjGJ JMdjd GdYLR GdZPGFj h SjGSGJ GdOYe, eJVefGJ JMQjQ GdJLGQI h GdGef GdZPGFj, BKGQ JMQjQ GdJLGQI GdRGQYjI aj ChVGY GdGef GdZPGFj GdYQHj, GdSjGSGJ GdhbGFjI ddCef GdZPGFj aj ehGLgI JMQjQ GdJLGQI GdRQGYjI, GdSjGSGJ GdGbJUGOjI GdRQGYjI, GdeYhfGJ GdZPGFjI, GdGReGJ GdGbJUGOjI, GdabQ h GdGeSGhGJ ` JQGLY OhdI GdQaGgjI GdGLJeGYjI, GdGef GdZPGFj GdYQHj aj YGde eJZjQ, GdbOQGJ GdCSGSjI h GdNjGQGJ GdGLJeGYjI, GdOhQ GdeYGUQ ddOhdI aj GdGbJUGOjGJ GdRRQGYjI GdYQHjI, HjFI GdGbJUGO GdYGdej h SjGSGJ GdGUdGM GdGbJUGOj, GTcGdjI GdCef GdZPGFj GdYQHj h GdNjGQGJ GdeYGUQI, eecfGJ h COGA GdCef GdZPGFj GdYQHjs
(3HHdjhZQGajG(B: (3U(B.247s
Keywords: (3GdGbJUGO GdZPGFjs; (3GdCef GdZPGFjs; (3GdCef GdZPGFj(B- (3GdHdOGf GdYQHjIs